2000
DOI: 10.1046/j.1537-2995.2000.40030335.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversion of initial blood flow to prevent whole‐blood contamination by skin surface bacteria: an in vitro model

Abstract: Development of a diversion system for collection of whole blood in sample tubes before filling the primary container may reduce the bioburden of subsequently prepared components and thereby the frequency of sepsis due to skin organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 20 publications
2
48
0
Order By: Relevance
“…Several recent studies suggest that the diversion of the initial 15 to 30 mL of whole blood from the main container might be associated with reduced risk of bacterial contamination. [54][55][56] Several blood bag manufacturers have developed plastic software to accommodate such an option. Several countries, including Canada, have recently introduced this intervention to try to reduce the rate of transfusion-associated sepsis.…”
Section: Removal Of First Aliquot Of Donor Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies suggest that the diversion of the initial 15 to 30 mL of whole blood from the main container might be associated with reduced risk of bacterial contamination. [54][55][56] Several blood bag manufacturers have developed plastic software to accommodate such an option. Several countries, including Canada, have recently introduced this intervention to try to reduce the rate of transfusion-associated sepsis.…”
Section: Removal Of First Aliquot Of Donor Bloodmentioning
confidence: 99%
“…63 Similar findings were also shown in an artificial model of blood collection. 56 The diversion pouch approach, using two recently FDA approved collection systems, is now being adopted by many blood centers as a way to lower the contamination risk. However, the ability of initial aliquot diversion to prevent clinical cases of transfusion-associated sepsis has not, as yet, been reported.…”
Section: Regulation and Regulatory Approachesmentioning
confidence: 99%
“…In a study which evaluated 3385 whole blood units collected using a special bag that allowed for the collection of two separated 15 ml aliquots at the beginning of venepuncture, bacteria were detected in at least one of the two aliquots taken in 2AE2% of blood units drawn (most, but not all, were detected only in the first aliquot) [16]. Moreover, Wagner et al reported that diverting the first 21-42 ml of saline or whole blood reduces the downstream bioburden of deliberately introduced surface Staphylococcus aureus by approximately 1 log [17].…”
Section: Removal Of the First Aliquot Of Donated Bloodmentioning
confidence: 99%
“…Several recent studies suggest that the diversion of the first 15 to 30 mL of blood from the main container might be associated with a reduced risk of bacterial contamination. [14][15][16] Several blood bag manufacturers have developed plastic software to accommodate such an option.…”
Section: Attempts To Decrease the Morbidity/mortality Riskmentioning
confidence: 99%